Investigating the Effectiveness of Flipped Classroom Strategy on Secondary School Students’ Achievement of Chemical Equilibrium in Chemistry - Oyakhirome, A. H. (NIU Journal of Social Sciences, 2025)
Looking at the tremendous impact that advancement in technology has made in the educational sector, this research investigated the effectiveness of flipped classroom strategy on secondary school students’ achievement of chemical equilibrium in Chemistry. The research employed a quasi-experimental design featuring a pre-test post-test non-equivalent control group. The study comprised 85 Senior Secondary School, 11chemistry randomly selected from two secondary schools. The assessment tool utilised was the Chemistry Chemical Equilibrium Test (CCET). The instrument had a reliability index of 0.79, as determined by the Kuder-Richardson (k21) formula analysis. The data were analysed using descriptive statistics of the mean to address the study issues, while independent sample t-tests was employed to evaluate the proposed hypotheses. The study's findings indicated that Chemistry students instructed using a flipped classroom instructional strategy achieved higher scores than those instructed with lectures method; additionally, no significant difference in the performance of male students taught with the flipped classroom instructional strategy. The study concluded that the flipped classroom instructional strategy is more effective in enhancing chemistry students' achievement compared to the lecture method. It is recommended that both teachers and students receive adequate training to develop the necessary skills for implementing this strategy and that they be encouraged to utilise it in teaching and learning. Keywords: Flipped Classroom Instructional Strategy, Sex, Chemical Equilibrium, Achievement, Quasi-Experimental Design.